Unexpected low-grade infections in revision hip arthroplasty for aseptic loosening: a single-institution experience of 274 hips. (1st June 2021) - Hipfl, Christian; Mooij, Wiebke; Perka, Carsten; Hardt, Sebastian; Wassilew, Georgi I.
Abstract : Aims: The purpose of this study was to evaluate unexpected positive cultures in total hip arthroplasty (THA) revisions for presumed aseptic loosening, to assess the prevalence of low-grade infection using two definition criteria, and to analyze its impact on implant survival after revision. Methods: A total of 274 THA revisions performed for presumed aseptic loosening from 2012 to 2016 were reviewed. In addition to obtaining intraoperative tissue cultures from all patients, synovial and sonication fluid samples of the removed implant were obtained in 215 cases (79%) and 101 cases (37%), respectively. Histopathological analysis was performed in 250 cases (91%). Patients were classified as having low-grade infections according to institutional criteria and Musculoskeletal Infection Society (MSIS) International Consensus Meeting (ICM) 2013 criteria. Low-grade infections according to institutional criteria were treated with targeted antibiotics for six weeks postoperatively. Implant failure was defined as the need for re-revision resulting from periprosthetic joint infection (PJI) and aseptic reasons. The mean follow-up was 68 months (26 to 95). Results: Unexpected positive intraoperative samples were found in 77 revisions (28%). Low-grade infection was diagnosed in 36 cases (13%) using institutional criteria and in nine cases (3%) using MSIS ICM 2013 criteria. In all, 41 patients (15%) had single specimen growth of a low-virulent pathogen and were deemed contaminated. Coagulase-negative Staphylococcus and anaerobes were the most commonly isolated bacteria. Implant failure for PJI was higher in revisions with presumed contaminants (5/41, 12%) compared to those with low-grade infections (2/36, 6%) and those with negative samples (5/197, 3%) (p = 0.021). The rate of all-cause re-revision was similar in patients diagnosed with low-grade infections (5/36, 14%) and those with presumed contaminants (6/41, 15%) and negative samples (21/197, 11%) (p = 0.699). Conclusion: Our findings suggest that the presumption of culture contamination in aseptic revision hip arthroplasty may increase the detection of PJI. In this cohort, the presence of low-grade infection did not increase the risk of re-revision. Further studies are needed to assess the relevance of single specimen growth and the benefits of specific postoperative antibiotic regimens. Cite this article: Bone Joint J  2021;103-B(6):1070–1077.